Reconstitution of functional influenza virus envelopes and fusion with membranes and liposomes lacking virus receptors. - Nussbaum, O (1987)
Reconstituted influenza virus envelopes were obtained following solubilization of intact virions with Triton X-100. Quantitative determination revealed that the hemolytic and fusogenic activities of the envelopes prepared by the present method were close or identical to those expressed by intact virions. Hemolysis as well as virus-membrane fusion occurred only at low pH values, while both activities were negligible at neutral pH values. Fusion of intact virions as well as reconstituted envelopes with erythrocyte membranes--and also with liposomes--was determined by the use of fluorescently labeled viral envelopes and fluorescence dequenching measurements. Fusion with liposomes did not require the presence of specific virus receptors, namely sialoglycolipids. Under hypotonic conditions, influenza virions or their reconstituted envelopes were able to fuse with erythrocyte membranes from which virus receptors had been removed by treatment with neuraminidase and pronase. Inactivated intact virions or reconstituted envelopes, namely, envelopes treated with hydroxylamine or glutaraldehyde or incubated at low pH or 85 degrees C, neither caused hemolysis nor possessed fusogenic activity. Fluorescence dequenching measurements showed that only fusion with liposomes composed of neutral phospholipids and containing cholesterol reflected the viral fusogenic activity needed for infection.